Combining narratives and modelling approaches to simulate fine scale and long-term urban growth scenarios for climate adaptation. (December 2016) - Houet, T.; Marchadier, C.; Bretagne, G.; Moine, M.P.; Aguejdad, R.; Viguié, V.; Bonhomme, M.; Lemonsu, A.; Avner, P.; Hidalgo, J.; Masson, V.
Abstract: Although climate scientists explore the effects of climate change for 2100, it is a challenging time frame for urban modellers to foresee the future of cities. The question addressed in this paper is how to improve the existing methodologies in order to build scenarios to explore urban climate impacts in the long term and at a fine scale. This study provides a structural framework in six steps that combines narratives and model-based approaches. The results present seven scenarios of urban growth based on land use strategies and technological and socio-economic trends. These contrasted scenarios span the largest possible world of futures for the city under study. Urban maps for 2010, 2040 and 2100 were used to assess the impacts on the Urban Heat Island. The comparison of these scenarios and related outputs allowed some levers to be evaluated for their capacity to limit the increase of air temperature. Highlights: Narrative scenarios of urban change are flexible and highly imaginative. Model-based scenarios of urban change allow for quantitative environmental assessment. A six-step method provides a framework for combining and benefiting from both approaches. Contrasting scenarios of urban change and their impacts on Urban Heat Island are simulated. The comparison of scenarios provides insights into key triggers to improve urban adaptation.